2013
DOI: 10.1123/jpah.10.5.699
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Improves Quality of Life in Indigenous Polynesian Peoples With Type 2 Diabetes and Visceral Obesity

Abstract: Exercise, regardless of specific modality, can improve many aspects of QoL in this population. Robust trials are required to investigate factors mediating improvements in QoL, and create greater advocacy for exercise as a QoL intervention in this and other indigenous populations with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(68 citation statements)
references
References 41 publications
2
63
0
Order By: Relevance
“…A pilot study on a team-based weight loss competition in Aboriginal communities from the New South Wales Ministry of Health was excluded due to lack of details on the baseline and post measurements [44]. One study from the peer-reviewed literature was excluded because of the overlap of data with another included study [47], leaving 13 studies [35, 36, 3943, 4853] in the synthesis. Three studies were published before 2000 [35, 39, 42], four between 2000–2010 [36, 43, 50, 52] and six between 2011 and 2015 [40, 41, 48, 49, 51, 53].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A pilot study on a team-based weight loss competition in Aboriginal communities from the New South Wales Ministry of Health was excluded due to lack of details on the baseline and post measurements [44]. One study from the peer-reviewed literature was excluded because of the overlap of data with another included study [47], leaving 13 studies [35, 36, 3943, 4853] in the synthesis. Three studies were published before 2000 [35, 39, 42], four between 2000–2010 [36, 43, 50, 52] and six between 2011 and 2015 [40, 41, 48, 49, 51, 53].…”
Section: Resultsmentioning
confidence: 99%
“…Implementation of a successful lifestyle intervention programme for New Zealand Māori to reduce the risk of type 2 diabetes and cardiovascular disease.To reduce the risk of type 2 diabetes and cardiovascular disease.Participants were prescribed individual diet and exercise programs. In addition, participants were invited to exercise sessions four times per week and a healthy food sessions once a month in the form of a cooking group.86%Mendham et al [41]Indigenous Australians, Regional New South Wales, Australia; RCT, N  = 26 (control n  = 10, intervention n  = 16);All male, age: 39.5 ± 10.6 years (intervention), 36.1 ± 16.1 years (control).A 12-week sports-based exercise programme for inactive Indigenous Australian men improved clinical risk factors associated with type 2 diabetes mellitus.To assess changes in clinical risk-factors following a 12-week exercise program.Supervised group-based cardiovascular and resistance exercises were conducted at a local fitness centre over 12 weeks.Intervention = 41%Control = 63%O’Dea [39]Indigenous Australians, Remote Western Australia, Australia; Cohort, n  = 14 (diabetics n  = 10, non-diabetics n = 4); Mixed, age: 59.3 ± 1.8 years (diabetics), 52.3 ± 4.3 years (non-diabetic).Marked improvement in carbohydrate and lipid metabolism in diabetic Australian Aborigines after temporary reversion to traditional lifestyle.Improve all aspects of carbohydrate and lipid metabolism that are linked to insulin resistance after temporary revision to traditional lifestyle.Participants were taken to a remote location and lived a hunter/gatherer lifestyle for 7 weeks.100%Rowley et al [35]Aboriginal Australians, Remote Western Australia, Australia; Cohort, n  = 96; Mixed gender, age: 49 ± 3 years (intervention), 43 ± 4 years (control).Effectiveness of a community-directed ‘healthy lifestyle’ program in a remote Australian aboriginal community.Assess the sustainability and effectiveness of a community-directed program for primary and secondary prevention of obesity, diabetes and cardiovascular disease in an Aboriginal Community.Formal and informal education sessions about nutrition, regular physical activity sessions such as hunting groups, sports (2–3 sessions) and walking groups (3–4 times per week, for an hour) and walking groups.51%Sukala et al [53]Polynesian (New Zealand Māori, Cook Island Māori, Samoan, Fijian, Tokelauan & Tongan), Porirua, New Zealand; Cohort, n  = 18 (females n  = 13, males n  = 5); Mixed genders, age: 49 ± 5 years.Exercise improves Quality of Life in Indigenous Polynesian peoples With type 2 diabetes and visceral obesity.The aim of the study was to evaluate the differential effects of 2, group-based exercise modalities on quality of life (QoL) in indigenous Polynesian peoples with type 2 diabetes (T2DM) and visceral obesity.Intervention included 3 exercise sessions per week (40–60minutes), consisting of resistance training and aerobic training.69% …”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that regular physical activity is the most effective method for improving insulin resistance [30]. Umpierre et al [31] reported that conducting a meta-analysis of 23 research results that involved an aerobic exercise showed that aerobic exercise is effective in improving insulin resistance, regardless of type, strength, time and frequency of training.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have consistently shown improved glycemic control [98][99][100][101][102][103], lipid profile [100,101], cardiovascular fitness [101,[104][105][106], antioxidant status [107,108], quality of life [109][110][111] and reduced inflammatory markers [108,[112][113][114][115][116], adiposity [103,[117][118][119][120] and atherogenic progression [113], establishing physical activity as an evidence-based treatment modality to combat diabesity. The joint position statement of ACSM and ADA [121] recommends undertaking exercise as a safe and effective measure for diabetes management and prescribes the following dose.…”
Section: Prevention and Therapymentioning
confidence: 99%